Prevalence of and Factors Associated with Sugar-sweetened Beverage Intake Among Women of Reproductive Age—12 States and District of Columbia, 2017 (P16-022-19). (13th June 2019) - Lundeen, Elizabeth; Park, Sohyun; Baidal, Jennifer A Woo; Sharma, Andrea; Blanck, Heidi M
Abstract: Objectives: Frequent sugar-sweetened beverage (SSB) intake is associated with weight gain and type 2 diabetes. There are limited data describing SSB intake among women of reproductive age (WRA). We described SSB intake patterns among pregnant and non-pregnant WRA, and identified characteristics associated with daily SSB intake. Methods: Using 2017 Behavioral Risk Factor Surveillance System data, we analyzed self-reported SSB intake for 392 pregnant and 11, 321 non-pregnant WRA (18–49 years). SSB intake (regular soda, fruit drinks, sweet tea, and sports/energy drinks) was measured in an optional module used by the District of Columbia and 12 states (AK, AZ, AR, DE, HI, IA, NY, NC, OH, VT, WV, WI). Multivariable logistic regression models were used to estimate adjusted odds ratios (aOR) for daily (≥1 time/day) SSB intake (ref: <1 time/day) by sociodemographic and behavioral characteristics. Results: Compared to non-pregnant women, a higher proportion of pregnant women were 18–29 years (51.1% vs 36.2%), married (58.3% vs 44.8%), nonsmokers (72.0% vs 67.8%), and had ≤ high school education (49.7% vs 36.3%). Overall, 27.3% of non-pregnant and 21.9% of pregnant women consumed SSB ≥1 time/day; 12.6% and 9.7%, respectively, consumed SSB ≥2 times/day. Among non-pregnant women, odds of SSB intake ≥1 time/day were higher for women who were non-Hispanic (NH) Black (aOR = 2.04, 95% CI = 1.55–2.69) compared to NH white; had ≤ high school education (aOR = 2.79, CI = 2.26–3.44) or some college (aOR = 1.85, CI = 1.50–2.27) vs college graduates; lived in nonmetropolitan counties (aOR = 1.35, CI = 1.11–1.63) vs metropolitan; had no leisure-time physical activity (aOR = 1.72, CI = 1.43–2.07) vs some; were former (aOR = 1.51, CI = 1.17–1.94) or current (aOR = 3.48, CI = 2.82–4.28] smokers vs nonsmokers. For pregnant women, only marital status was significant: those not married had higher odds (aOR = 2.81, CI = 1.05–7.51) for daily SSB intake than married women. Conclusions: Reducing SSB intake is a strategy to maintain a healthy weight, particularly in pregnancy when added calories should be nutrient rich. Information from monitoring SSB intake among WRA can be used to promote healthy pre-pregnancy weight and pregnancy weight gain, which can reduce the risk of adverse maternal and infant health outcomes. Funding Sources: CDC.